Multi-layer composite circuit board preparation method and multi-layer composite circuit board

By using ceramic-based powder and nanometal particles in the multi-layer composite circuit board, a material with a continuous thermal conductivity network and microporous structure is formed, and the thermal through-holes and microporous layers are solved by vacuum hot pressing and setting of thermal conductivity, thermal stress and insufficient seismic performance are achieved, and a multi-layer composite circuit board with high thermal conductivity, high strength, high insulation and high seismic performance is achieved.

CN119653647AActive Publication Date: 2025-03-18GUANGDONG JINSHUN TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510174434.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

The existing multi-layer composite circuit boards have problems such as uneven thermal conductivity, interlayer peeling or cracks caused by thermal stress, and insufficient seismic resistance in high temperature and high vibration environments.

Method used

By mixing the ceramic-based powder with nanometal particles, a thermally conductive microporous ceramic material with a continuous thermal conductivity network and a microporous structure is formed, and a composite substrate is formed by vacuum heat pressing, and a thermal through-hole and a microporous layer are provided to form a multi-layer structure.

Benefits of technology

It significantly improves thermal conductivity, relieves thermal and mechanical stresses, enhances the overall stability and seismic resistance of multi-layer composite circuit boards, and ensures that the equipment maintains a reliable and stable working state in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653647A_ABST
    Figure CN119653647A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of circuit board preparation, and discloses a multilayer composite circuit board preparation method and a multilayer composite circuit board, and the method comprises the steps: mixing ceramic-based powder with nano metal particles, and carrying out sintering to form a heat-conducting microporous ceramic material with a continuous heat-conducting network and a microporous structure; a plurality of heat-conducting microporous ceramic materials are laminated and then pressed into a composite substrate through vacuum hot pressing, and through heat-conducting through holes are formed in the composite substrate; the composite substrates with the heat conduction through holes are stacked, a micropore layer used for heat conduction and shock absorption is arranged between every two adjacent composite substrates, and the stacked composite substrates and the micropore layers are subjected to vacuum hot pressing to form a multi-layer structure. According to the multi-layer composite circuit board preparation method and the multi-layer composite circuit board, through the continuous heat conduction network, the micropore structure and the micropore layer, the heat conduction performance is remarkably improved, thermal stress and mechanical stress are effectively released through the elastic characteristic of the micropore structure, and the overall stability of the multi-layer composite circuit board is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of circuit board preparation, and in particular to a method for preparing a multilayer composite circuit board and a multilayer composite circuit board. Background Art

[0002] With the rapid development of electronic technology, the application scope of electronic equipment continues to expand, from consumer electronics to automotive electronics to aerospace, and the performance requirements of electronic equipment are also constantly improving. In particular, high-performance electronic equipment, such as autonomous driving systems, 5G communication equipment, and high-frequency radar systems, have put forward higher requirements for multi-layer composite electronic circuit boards. These application scenarios not only require multi-layer composite circuit boards to have high conductivity and reliable electrical insulation performance, but also require them to have excellent thermal management performance and shock resistance to ensure the stability and reliability of the equipment under high-speed operation and complex environments.

[0003] In the prior art, methods for preparing multi-layer composite circuit boards typically incorporate thermally conductive materials into the multi-layer structure to improve the heat dissipation performance of the circuit board. However, in traditional methods, the thermally conductive material is typically dispersed within the substrate material (i.e., insulating material), resulting in a discontinuous heat conduction path. For example, when used in radar sensor modules used in autonomous driving systems, these radar sensor modules need to be installed at the front of the vehicle. These modules need to operate stably in various weather conditions (such as high and low temperatures and humid environments) and must withstand severe vibration and impact during high-speed driving. When operating in the high-temperature environment at the front of the vehicle, the low heat conduction efficiency can easily lead to localized overheating. Due to the large difference in thermal expansion coefficient between the thermally conductive material and the substrate material (i.e., insulating material), the low heat conduction efficiency of the thermally conductive material can easily generate thermal stress during thermal cycling, leading to interlayer delamination or cracking, affecting the long-term stability of the multi-layer composite circuit board substrate. Furthermore, in high-vibration environments, the multi-layer structure of traditional multi-layer composite circuit boards is easily damaged, and the insufficient bonding strength between the thermally conductive material and the substrate material (i.e., insulating material) leads to poor seismic performance. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a multi-layer composite circuit board and a multi-layer composite circuit board. By having a continuous heat-conducting network, a microporous structure and a microporous layer, not only the thermal conductivity is significantly improved, but also the elastic properties of the microporous structure effectively relieve thermal stress and mechanical stress, thereby enhancing the overall stability and seismic resistance of the multi-layer composite circuit board.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: Design a method for preparing a multilayer composite circuit board, including: S100, mixing ceramic-based powder with nano-metal particles, and sintering to form a thermally conductive microporous ceramic material having a continuous thermal conductive network and a microporous structure; S200, stacking a plurality of thermally conductive microporous ceramic materials and pressing them into a composite substrate by vacuum hot pressing, and forming through thermal conductive holes on the composite substrate; S300, stacking the composite substrates formed with thermal vias, providing a microporous layer for heat conduction and shock absorption between adjacent composite substrates, forming a multilayer structure by vacuum hot pressing the stacked composite substrates and the microporous layer, and performing surface coating on the multilayer structure to prepare a multi-layer composite circuit board substrate.

[0006] Optionally, the ceramic-based powder is at least one of aluminum oxide powder and silicon nitride powder, and the nano-metal particles are at least one of nano-copper particles and silver particles.

[0007] Optionally, the S100 specifically includes: S110, mixing the aluminum oxide powder and the nano-copper particles, and uniformly dispersing them by mechanical stirring to form a preliminary mixture; S120, placing the preliminary mixture in an electrostatic spraying device, preparing the preliminary mixture into uniform particles by low-pressure electrostatic spraying, wherein the particle size is between 100 and 300 microns, and then placing the uniform particles in a cold isostatic pressing device, and performing pre-pressing at a pressure of 100 to 200 MPa to obtain a powder blank; S130, placing the powder blank in a mixing device, and evenly spraying the polymethacrylate solution on the surface of the powder blank through a fine mist nozzle, and then placing the powder blank sprayed with the polymethacrylate solution in a drying oven and drying it at a temperature range of 50° C. to 70° C., so that the solvent gradually evaporates and the polymethacrylate is evenly attached to the surface of the powder blank; S140, placing the powder blank with polymethacrylate attached thereto in a high-temperature sintering furnace and sintering the blank by increasing the temperature in stages. During the sintering process, the nano-copper particles are combined with the alumina powder by liquid-phase diffusion in the alumina powder to form a heat conduction path. Under nitrogen protection, oxidation of the particles is suppressed, and the polymethacrylate is volatilized at high temperature, so that the powder blank forms a uniformly distributed microporous structure, wherein the pore diameter of the micropores is controlled to be between 5 and 20 microns, thereby obtaining a heat-conducting microporous ceramic material. S150, placing the sintered thermally conductive microporous ceramic material in a low-temperature annealing furnace, and annealing it at a temperature range of 500° C. to 700° C. for 1 to 2 hours to release the residual stress of the thermally conductive microporous ceramic material during the sintering process.

[0008] Optionally, the S110 specifically includes: S111, placing the aluminum oxide powder in an ultrasonic oscillation device, washing it with deionized water to remove adsorbed impurities on the surface of the aluminum oxide powder, placing the washed aluminum oxide powder in a drying oven, and drying it at a constant temperature of 80° C. to 120° C. for 4 to 6 hours; S112, selecting nano-copper particles with a particle size ranging from 20 to 50 nanometers, placing them in a silane coupling agent solution, and mechanically stirring for 30 to 60 minutes to form an active coating on the surface of the nano-copper particles, and performing a low-temperature drying treatment on the nano-copper particles with the active coating to obtain surface-activated nano-copper particles; S113. Dry-mix the cleaned alumina powder and the surface-activated nano-copper particles in a mass ratio of 1:0.2 to 0.5 using a high-energy ball mill. The milling time of the high-energy ball mill is controlled to be 6 to 8 hours. Zirconia ceramic balls are used as the ball milling medium to form a preliminary mixture.

[0009] Optionally, the S140 specifically includes: S141, placing the powder blank with polymethacrylate attached thereto in a high-temperature sintering furnace, and performing an initial heating stage, wherein the temperature is raised from room temperature to 600° C. at a heating rate of 5° C. per minute, and maintained for 1 hour; S142, after the initial heating stage, an intermediate heating stage is performed, in which the temperature is raised from 600° C. to 900° C. at a heating rate of 10° C. per minute and maintained for 2 hours; S143, after the intermediate heating stage is completed, a high-temperature sintering stage is performed, in which the temperature is raised from 900° C. to 1300° C. at a heating rate of 8° C. per minute and maintained for 3 to 4 hours, so that the nano-copper particles form a continuous heat-conducting network in the alumina powder through liquid phase diffusion; S144. During the high-temperature sintering stage, a nitrogen protective atmosphere is maintained in the high-temperature sintering furnace to prevent oxidation of the nano-copper particles. The polymethacrylate volatilizes at high temperatures, thereby forming a uniformly distributed microporous structure in the powder blank. S145. After the high-temperature sintering stage is completed, a slow cooling stage is performed, in which the temperature is slowly lowered to room temperature at a cooling rate of 5°C per minute.

[0010] Optionally, before S200, an insulating material is mixed with an electrical insulating filler to prepare an insulating coating material, and the insulating coating material is coated on the surfaces of the plurality of thermally conductive microporous ceramic materials. S200 specifically includes: S210, stacking a plurality of thermally conductive microporous ceramic materials and placing them in a vacuum hot press, and hot-pressing the stacked plurality of thermally conductive microporous ceramic materials into a composite substrate by the vacuum hot press; S220, drilling a hole on the composite substrate using a laser drilling device to form a thermal via hole penetrating the composite substrate, and performing an ultrasonic cleaning process on the composite substrate with the thermal via hole to remove debris and impurities generated during the drilling process; S230, after cleaning the composite substrate with the thermal via formed thereon, performing a metallization treatment on the inner wall of the thermal via to uniformly form a copper film having thermal conductivity and electrical connection properties on the inner wall of the thermal via; S240. After forming a copper film on the inner wall of the thermal via, the composite substrate is placed in a high-temperature annealing furnace and annealed at 300° C. to 500° C. for 1 hour. During the annealing process, the copper film on the inner wall of the thermal via is combined with the continuous heat conduction network formed by the nano-copper particles in the composite substrate to form a continuous heat conduction path.

[0011] Optionally, the S230 specifically includes: S231, immersing the cleaned composite substrate in a chemical plating solution containing copper ions, and uniformly depositing a copper film having thermal conductivity and electrical connection properties on the inner wall of the thermal via hole; S232, electroplating the thermal via hole on which a layer of copper film is deposited, and further increasing the thickness of the copper film on the inner wall of the thermal via hole by electroplating.

[0012] Optionally, the S300 specifically includes: S310, mixing polyurethane particles and carbon fiber filler in a mass ratio to obtain a composite material for preparing a microporous layer; S320, placing the composite material for preparing the microporous layer in a mold for pre-pressing to obtain the microporous layer; S330, placing the microporous layer between adjacent layers of the composite substrate, coating the surface of the microporous layer with silicone-based adhesive to bond it to the adjacent composite substrate, and then performing vacuum hot pressing to form a multi-layer structure, performing corrosion-resistant coating on the surface of the multi-layer structure to obtain a multi-layer composite circuit board substrate.

[0013] A multilayer composite circuit board is prepared using the above-mentioned multilayer composite circuit board preparation method, wherein the multilayer composite circuit board comprises: Thermally conductive microporous ceramic material, made by hot-pressing a mixture of alumina powder and nano-copper particles, is used for lamination and vacuum hot-pressing to form a composite substrate; Continuous heat-conducting network and microporous structure are formed in the thermally conductive microporous ceramic material to provide a heat conduction path and absorb external mechanical impact; Thermal vias are provided on the surface of the composite substrate and are connected to the continuous thermal conductive network to form a continuous thermal conductive path to improve thermal conductivity and electrical connection performance; The microporous layer is disposed between the composite substrates to optimize shock absorption and thermal stability.

[0014] The present invention provides a method for preparing a multi-layer composite circuit board and a multi-layer composite circuit board, which have the following beneficial effects: The multi-layer composite circuit board preparation method and the multi-layer composite circuit board are characterized by mixing ceramic-based powder with nano-metal particles and then sintering the nano-metal particles to form a continuous thermal conductive network structure and microporous structure in the ceramic-based powder. This not only provides a good heat conduction path and improves the overall thermal conductivity, but also enhances the mechanical strength, adhesion and seismic resistance of the material through the microporous structure. The thermal conductive holes enable each layer of thermally conductive microporous ceramic material to be tightly bonded, ensuring effective heat transfer between the layers of thermally conductive microporous ceramic material, thereby achieving high thermal conductivity, high strength, high insulation and high seismic resistance of the multi-layer composite circuit board. The microporous layer in the multi-layer structure formed by the composite substrate further improves the seismic resistance and environmental resistance of the circuit board, enabling it to maintain a reliable and stable working state under complex working conditions. Finally, the surface coating treatment enhances the corrosion resistance of the material, giving the multi-layer composite circuit board excellent electrical insulation performance and extending the service life of the multi-layer composite circuit board. By optimizing the heat conduction path, enhancing interlayer bonding and shock absorption, the problems of uneven heat conduction, poor structural stability and insufficient seismic resistance are effectively avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0016] The structures, proportions, sizes, etc. depicted in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not intended to limit the conditions under which the present invention can be implemented and therefore have no substantive technical significance. Any structural modifications, changes in proportional relationships, or adjustments in size should still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and objectives that can be achieved by the present invention.

[0017] Figure 1 This is one of the flow charts of the method for preparing a multi-layer composite circuit board according to Example 1. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative work shall fall within the scope of protection of the present invention.

[0019] Example 1: See also Figure 1 The present invention provides a technical solution: a method for preparing a multi-layer composite circuit board, comprising: S100, mixing ceramic-based powder with nano-metal particles, and sintering to form a thermally conductive microporous ceramic material having a continuous thermal conductive network and a microporous structure; S200, stacking a plurality of thermally conductive microporous ceramic materials and pressing them into a composite substrate by vacuum hot pressing, and forming through thermal conductive holes on the composite substrate; S300, stacking composite substrates formed with thermal vias, providing microporous layers for heat conduction and shock absorption between adjacent composite substrates, subjecting the stacked composite substrates and the microporous layers to vacuum hot pressing to form a multilayer structure, and coating the multilayer structure to produce a multilayer composite circuit board substrate; The ceramic-based powder is at least one of aluminum oxide powder and silicon nitride powder, and the nano-metal particles are at least one of nano-copper particles and silver particles; In step S100, a ceramic-based powder is mixed with nano-metal particles and sintered to form a thermally conductive microporous ceramic material having a continuous thermal conductive network and a microporous structure. Specifically, alumina powder or silicon nitride powder is used as the ceramic-based powder, and the nano-metal particles are selected from nano-copper particles or nano-silver particles. By precisely controlling the sintering parameters, the nano-metal particles form a continuous thermal conductive network in the ceramic matrix and generate a microporous structure at the same time. The microporous structure not only significantly improves the thermal conductivity of the material, but also provides good mechanical strength and stability. The continuous thermal conductive network is an interconnected network structure formed by high thermal conductivity materials (such as nano-metal particles) in a matrix material (such as ceramic-based powder). During the sintering process, the nano-metal particles form a continuous thermal conductive path through liquid or solid phase diffusion, which significantly improves the overall thermal conductivity of the material. In traditional multiphase composite materials, the matrix material with poor thermal conductivity and the high thermal conductivity There will be interfacial thermal resistance between fillers, which will significantly reduce the thermal conductivity of the material. The continuous thermal conductive network reduces the interfacial thermal resistance by forming a good interface bond, ensuring that heat can be efficiently transferred from one particle to another, thereby improving the overall thermal conductivity. The continuous thermal conductive network provides a clear transfer path for heat, reducing the loss of heat due to random diffusion in the matrix material, allowing heat to be transferred in a concentrated manner, and improving the thermal conductivity efficiency. The air or other filling materials in the pores formed by the microporous structure can transfer heat through convection and radiation, further improving the thermal conductivity efficiency. The microporous structure has certain elastic properties, which can effectively relieve the stress caused by thermal expansion, avoid cracks or delamination of the material during the thermal cycle, and ensure the structural stability of the material. The reduction of thermal expansion stress helps to maintain the integrity of the thermal conductive network and avoid the breakage of the thermal conductive path due to stress concentration, thereby improving the long-term thermal conductivity of the material. In step S200, the prepared thermally conductive microporous ceramic materials are stacked and arranged in layers. The materials are then pressed in a vacuum hot press under high temperature and high pressure to ensure that the layers are tightly bonded together, forming an integrated composite substrate. Subsequently, through-hole thermal vias are formed in the composite substrate using a drilling device to ensure that heat can be efficiently transferred throughout the multi-layer structure, further optimizing the heat dissipation performance and overall mechanical strength of the circuit board. In step S300, a microporous layer material with thermal conductivity and shock absorption is filled between adjacent composite substrates. Through a hot pressing process in a vacuum environment, the interlayer materials are tightly bonded to form a multi-layer composite structure with excellent thermal conductivity and shock absorption effects. Finally, the multi-layer structure is surface coated to enhance its environmental resistance and protection capabilities, ultimately producing a high-performance multi-layer composite circuit board substrate. This design not only improves the thermal conductivity of the circuit board, but also effectively relieves thermal expansion and mechanical stress, thereby improving the overall shock resistance and long-term reliability.

[0020] In this embodiment, as a preferred solution, S100 specifically includes: S110, mixing the aluminum oxide powder and the nano-copper particles, and uniformly dispersing them by mechanical stirring to form a preliminary mixture; S120, placing the preliminary mixture in an electrostatic spraying device, preparing the preliminary mixture into uniform particles by low-pressure electrostatic spraying, wherein the particle size is between 100 and 300 microns, and then placing the uniform particles in a cold isostatic pressing device, and performing pre-pressing at a pressure of 100 to 200 MPa to obtain a powder blank; S130, placing the powder blank in a mixing device, and evenly spraying the polymethacrylate solution on the surface of the powder blank through a fine mist nozzle, and then placing the powder blank sprayed with the polymethacrylate solution in a drying oven and drying it at a temperature range of 50° C. to 70° C., so that the solvent gradually evaporates and the polymethacrylate is evenly attached to the surface of the powder blank; S140, placing the powder blank with polymethacrylate attached in a high-temperature sintering furnace and sintering by increasing the temperature in stages. During the sintering process, the nano-copper particles are combined with the alumina powder through liquid-phase diffusion in the alumina powder to form a heat conduction path, and the particle oxidation is suppressed under nitrogen protection. At the same time, volatile polymethacrylate is added to the powder blank. The polymethacrylate volatilizes at high temperature, so that the powder blank forms a uniformly distributed microporous structure. The pore size of the micropores is controlled to be between 5 and 20 microns, thereby obtaining a thermally conductive microporous ceramic material. By adjusting the content and particle distribution of the polymethacrylate, the microporous structure is ensured to be uniform and stable. This microporous structure not only provides a heat conduction path but also can absorb external mechanical shock to achieve a shock absorption effect. S150, placing the sintered thermally conductive microporous ceramic material in a low-temperature annealing furnace, and annealing it at a temperature range of 500° C. to 700° C. for 1 to 2 hours to release the residual stress of the thermally conductive microporous ceramic material during the sintering process, thereby further improving the thermal conductivity and structural stability of the thermally conductive microporous ceramic material; In step S110, a certain proportion of alumina powder and nano-copper particles are added to a mixing container, and stirred using a high-speed mechanical stirring device to ensure that the nano-copper particles are evenly distributed in the alumina powder. Through mechanical stirring, the nano-copper particles can form a preliminary dispersion in the alumina matrix, laying the foundation for the formation of a thermal conductive network in the subsequent sintering process. In step S120, the preliminary mixture is placed in an electrostatic spraying device, and the preliminary mixture is prepared into uniform particles by low-pressure electrostatic spraying. The particle size is controlled between 100 and 300 microns, and the electrostatic force is used to ensure the uniformity of the particles. Subsequently, these uniform particles are placed in a cold isostatic pressing device and pre-pressed at a pressure of 100 to 200 MPa to obtain a powder blank with a dense structure. This process uses high-pressure pressing to make the contact between the particles closer. In step S140, the powder blank is placed in a high-temperature sintering furnace and sintered by separation. The temperature is raised in stages for sintering. During the sintering process, the nano-copper particles are combined with the alumina matrix in the alumina powder through liquid phase diffusion to form a continuous heat conduction path. To prevent the oxidation of the nano-copper particles, the sintering is carried out under a nitrogen protective atmosphere. In addition, volatile polymethacrylate is added to the powder blank during the sintering process. The polymethacrylate volatilizes at high temperature to form a uniformly distributed microporous structure. The pore size of the microporous structure is controlled between 5 and 20 microns. By adjusting the content and particle distribution of polymethacrylate, the uniformity and stability of the microporous structure are ensured. This microporous structure not only provides an excellent heat conduction path, but also can absorb external mechanical shock to achieve a shock absorption effect. The purpose of annealing is to release the residual stress of the thermally conductive microporous ceramic material during the sintering process, further improve the thermal conductivity and structural stability of the material, and gradually release the stress inside the material by controlling the temperature and time to improve the overall performance of the material. The polymethacrylate powder is added to ethanol or acetone in a certain mass ratio (for example, a mass concentration of 5% to 10%), and is fully dissolved by mechanical stirring or ultrasonic treatment at room temperature to form a uniform polymethacrylate solution. The pre-pressed powder blank is placed in a rotating mixing device, and the prepared polymethacrylate solution is evenly sprayed on the surface of the powder blank through a fine mist nozzle. The rotating mixing device rotates at an appropriate speed (i.e., 30 to 50 RPM), preferably 40 RPM, to ensure that the polymethacrylate solution can evenly cover each particle of the powder blank. The spraying process In the process, the spraying time and spraying amount are controlled to ensure that each gram of powder blank evenly absorbs a certain amount of polymethacrylate solution (for example, each gram of powder blank absorbs 0.1 to 0.5 ml of polymethacrylate solution), and the mixing time is controlled within 30 to 60 minutes to ensure that the polymethacrylate solution is completely and evenly distributed on the surface of the powder blank. The powder blank sprayed with the polymethacrylate solution is transferred to a low-temperature drying oven and dried at a temperature range of 50°C to 70°C for 2 to 4 hours. During the drying process, the solvent gradually evaporates and the polymethacrylate is evenly attached to the surface of the powder blank.

[0021] In this embodiment, as a preferred solution, S110 specifically includes: S111. Placing the aluminum oxide powder in an ultrasonic oscillation device and washing it with deionized water to remove adsorbed impurities on the surface of the aluminum oxide powder. Placing the washed aluminum oxide powder in a drying oven and drying it at a constant temperature of 80° C. to 120° C. for 4 to 6 hours to ensure that the aluminum oxide powder is dry and has a clean surface to facilitate subsequent uniform mixing with the nano-metal particles. S112. Select nano-copper particles with a particle size range of 20 to 50 nanometers, place them in a silane coupling agent solution, and mechanically stir for 30 to 60 minutes to form an active coating on the surface of the nano-copper particles to enhance the interfacial bonding between the particles and the ceramic base powder. Low-temperature drying the nano-copper particles with the active coating to obtain surface-activated nano-copper particles. S113. The cleaned alumina powder and the surface-activated nano-copper particles are dry-mixed in a high-energy ball mill at a mass ratio of 1:0.2 to 0.5. The milling time of the high-energy ball mill is controlled at 6 to 8 hours. Zirconia ceramic balls are used as the milling medium to form a preliminary mixture to ensure uniform mixing. During the ball milling process, the rotation speed (300 to 400 rpm) and temperature are controlled to avoid particle agglomeration and ensure uniform distribution of the ceramic-based powder and the nano-metal particles.

[0022] In this embodiment, as a preferred solution, S140 specifically includes: S141. Placing the powder blank with polymethacrylate attached thereto in a high-temperature sintering furnace for an initial heating stage. During the initial heating stage, the temperature is raised from room temperature to 600° C. at a heating rate of 5° C. per minute and maintained for 1 hour. The purpose of this stage is to remove residual adsorbed gas and organic matter to ensure the purity of the material in the subsequent sintering process. S142. After the initial heating stage, an intermediate heating stage is performed, in which the temperature is raised from 600° C. to 900° C. at a heating rate of 10° C. per minute and maintained for 2 hours. The purpose of this stage is to promote a preliminary reaction between the ceramic matrix (i.e., alumina powder) and the nano-metal particles (i.e., nano-copper particles) to form a preliminary bonding interface. S143. After the intermediate heating stage, a high-temperature sintering stage is performed. In the high-temperature sintering stage, the temperature is raised from 900° C. to 1300° C. at a heating rate of 8° C. per minute and maintained for 3 to 4 hours, so that the nano-copper particles form a continuous heat-conducting network in the alumina powder through liquid phase diffusion. This stage ensures the optimization of the material's density and thermal conductivity. S144. During the high-temperature sintering stage, a nitrogen protective atmosphere is maintained in the high-temperature sintering furnace to prevent oxidation of the nano-copper particles. The polymethacrylate volatilizes at high temperatures, thereby forming a uniformly distributed microporous structure in the powder blank. By adjusting the polymethacrylate content (e.g., 0.5% to 2%) and particle size, the pore size of the microporous structure is controlled to be between 5 and 20 microns, thereby ensuring the uniformity and stability of the microporous structure. S145. After the high-temperature sintering stage, a slow cooling stage is carried out, in which the material is slowly cooled to room temperature at a cooling rate of 5°C per minute to avoid micro cracks inside the material due to excessive temperature differences.

[0023] In this embodiment, as a preferred solution, before S200, an insulating material is mixed with an electrical insulating filler to prepare an insulating coating material, and the insulating coating material is coated on the surfaces of the plurality of thermally conductive microporous ceramic materials. S200 specifically includes: S210, stacking a plurality of thermally conductive microporous ceramic materials and placing them in a vacuum hot press, and hot-pressing the stacked plurality of thermally conductive microporous ceramic materials into a composite substrate by the vacuum hot press; S220. Drilling a hole on the composite substrate using a laser drilling device to form a thermal via hole penetrating the composite substrate. Ultrasonic cleaning is performed on the composite substrate with the thermal via hole to remove debris and impurities generated during the drilling process. The laser drilling device is used to drill the hole. The laser drilling precisely controls the laser power, pulse frequency, and focal length to ensure consistent and perpendicular apertures. The aperture range is controlled between 50 and 200 microns. S230, after the composite substrate with the thermal via formed thereon is cleaned, metallizing the inner wall of the thermal via to uniformly form a copper film having thermal conductivity and electrical connection performance on the inner wall of the thermal via to improve the thermal conductivity and electrical connection performance; Use an ultrasonic cleaning tank to soak the composite substrate in a mixture of deionized water and an appropriate amount of chemical cleaning agent (such as hydrofluoric acid or nitric acid). Control the ultrasonic cleaning time to 10 to 20 minutes to ensure that the inner wall of the hole is clean and free of residue; S240. After forming a copper film on the inner wall of the thermal via, the composite substrate is placed in a high-temperature annealing furnace and annealed at 300°C to 500°C for 1 hour. During the annealing process, the copper film on the inner wall of the thermal via is combined with the continuous thermal conductive network formed by the nano-copper particles in the composite substrate to form a continuous thermal conductive path. The annealing treatment enhances the bonding strength between the via and the continuous thermal conductive network to ensure efficient heat transfer.

[0024] In this embodiment, as a preferred solution, S230 specifically includes: S231, immersing the cleaned composite substrate in a chemical plating solution containing copper ions, and uniformly depositing a copper film having thermal conductivity and electrical connection properties on the inner wall of the thermal via hole; using a chemical copper plating process, immersing the composite substrate in the chemical plating solution containing copper ions, and uniformly depositing a copper film on the inner wall of the thermal via hole by controlling the reaction temperature (50° C. to 70° C.) and time (30 to 60 minutes); S232. Electroplating is performed on the thermal via hole on which a layer of copper film is deposited. The thickness of the copper film on the inner wall of the thermal via hole is further increased by electroplating to ensure the thermal and electrical conductivity of the thermal via hole.

[0025] In this embodiment, as a preferred solution, S300 specifically includes: S310, mixing polyurethane particles and carbon fiber filler in a mass ratio to obtain a composite material for preparing a microporous layer; the elastic polymer particles decompose during a subsequent sintering process to form a microporous structure with a certain elasticity, and the shock-absorbing reinforcing filler further optimizes the shock-absorbing performance and thermal stability of the microporous layer; the mixed material is uniformly mixed in a vacuum environment for 3 to 5 hours to ensure uniform distribution of the components; S320, placing the composite material for preparing the microporous layer in a mold for pre-pressing to obtain the microporous layer; S330, placing a microporous layer between adjacent layers of a composite substrate, bonding the microporous layer to the adjacent composite substrate by coating a silicone-based adhesive on the surface of the microporous layer, and then performing vacuum hot pressing to form a multi-layer structure, performing a corrosion-resistant coating on the surface of the multi-layer structure, and producing a multi-layer composite circuit board substrate; Thermal vias are opened on the composite substrate, and secondary vias are opened in the microporous layer corresponding to the thermal vias. A layer of copper film with thermal conductivity and electrical connection performance is deposited on the secondary vias and the thermal vias and electroplated. The thickness of the copper film on the inner wall of the thermal vias is further increased by electroplating to ensure the thermal and electrical conductivity of the thermal vias. Alternatively, secondary conductive holes can be opened in the microporous layer corresponding to the thermal conductive holes. When the microporous layer is placed between adjacent layers of the composite substrate, the surface of the microporous layer is coated with silicone-based adhesive to bond it to the adjacent composite substrate, and then vacuum hot pressing is performed to form a multi-layer structure. A copper layer is then coated on the microporous layer portion of the multi-layer structure to form a connected conductive path.

[0026] The present invention also provides a multilayer composite circuit board, which is prepared using the above-mentioned multilayer composite circuit board preparation method, and the multilayer composite circuit board comprises: Thermally conductive microporous ceramic material, made by hot-pressing a mixture of alumina powder and nano-copper particles, is used for lamination and vacuum hot-pressing to form a composite substrate; Continuous heat-conducting network and microporous structure are formed in the thermally conductive microporous ceramic material to provide a heat conduction path and absorb external mechanical impact; Thermal vias are provided on the surface of the composite substrate and are connected to the continuous thermal conductive network to form a continuous thermal conductive path to improve thermal conductivity and electrical connection performance; The microporous layer is disposed between the composite substrates to optimize shock absorption and thermal stability.

[0027] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a multilayer composite circuit board, characterized in that: include: S100, mixing ceramic-based powder with nano-metal particles, and sintering to form a thermally conductive microporous ceramic material having a continuous thermally conductive network and a microporous structure; S200, stacking a plurality of thermally conductive microporous ceramic materials and pressing them into a composite substrate by vacuum hot pressing, and forming a through thermal conductive hole on the composite substrate; S300, stacking composite substrates formed with thermal vias, setting microporous layers for heat conduction and shock absorption between adjacent composite substrates, forming a multilayer structure through vacuum hot pressing of the stacked composite substrates and the microporous layers, and coating the surface of the multilayer structure to obtain a multi-layer composite circuit board substrate.

2. The method for preparing a multilayer composite circuit board according to claim 1, characterized in that: The ceramic-based powder is at least one of aluminum oxide powder and silicon nitride powder, and the nano-metal particles are at least one of nano-copper particles and silver particles.

3. The method for preparing a multilayer composite circuit board according to claim 2, characterized in that: The S100 specifically includes: S110, mixing the aluminum oxide powder and the nano copper particles, and uniformly dispersing them by mechanical stirring to form a preliminary mixture; S120, placing the preliminary mixture in an electrostatic spraying device, preparing the preliminary mixture into uniform particles by low-pressure electrostatic spraying, wherein the particle size is between 100 and 300 microns, and then placing the uniform particles in a cold isostatic pressing device, performing pre-pressing molding at a pressure of 100 to 200 MPa to obtain a powder blank; S130, placing the powder blank in a mixing device, spraying the polymethacrylate solution evenly on the surface of the powder blank through a fine mist nozzle, and then placing the powder blank sprayed with the polymethacrylate solution in a drying oven for drying at a temperature range of 50° C. to 70° C., wherein the solvent gradually evaporates and the polymethacrylate is evenly attached to the surface of the powder blank; S140, placing the powder blank with polymethacrylate attached thereto in a high-temperature sintering furnace, and sintering by increasing the temperature in stages. During the sintering process, the nano-copper particles are combined with the alumina powder in the alumina powder by liquid phase diffusion to form a heat conduction path, and the oxidation of the particles is suppressed under the protection of nitrogen. The polymethacrylate volatilizes at a high temperature, so that the powder blank forms a uniformly distributed microporous structure, and the pore size of the micropores is controlled to be between 5 and 20 microns, thereby obtaining a heat-conducting microporous ceramic material; S150, placing the sintered thermally conductive microporous ceramic material in a low-temperature annealing furnace, and annealing it at a temperature range of 500° C. to 700° C. for 1 to 2 hours to release the residual stress of the thermally conductive microporous ceramic material during the sintering process.

4. The method for preparing a multilayer composite circuit board according to claim 3, characterized in that: The S110 specifically includes: S111, placing the aluminum oxide powder in an ultrasonic oscillation device, washing it with deionized water to remove adsorbed impurities on the surface of the aluminum oxide powder, placing the washed aluminum oxide powder in a drying oven, and drying it at a constant temperature of 80° C. to 120° C. for 4 to 6 hours; S112, selecting nano copper particles with a particle size ranging from 20 to 50 nanometers, placing them in a silane coupling agent solution, and mechanically stirring them for 30 to 60 minutes to form an active coating on the surface of the nano copper particles, and subjecting the nano copper particles with the active coating to low temperature drying treatment to obtain surface activated nano copper particles; S113. Dry-mix the cleaned alumina powder and the surface-activated nano-copper particles in a mass ratio of 1:0.2-0.5 using a high-energy ball mill. The milling time of the high-energy ball mill is controlled at 6 to 8 hours. Zirconia ceramic balls are used as the ball milling medium to form a preliminary mixture.

5. The method for preparing a multi-layer composite circuit board according to claim 3, characterized in that: The S140 specifically includes: S141, placing the powder blank in a high-temperature sintering furnace for an initial heating stage, during which the temperature is raised from room temperature to 600° C. at a heating rate of 5° C. per minute and maintained for 1 hour; S142, after the initial heating stage, an intermediate heating stage is performed, in which the temperature is increased from 600° C. to 900° C. at a heating rate of 10° C. per minute and maintained for 2 hours; S143, after the intermediate heating stage is completed, a high temperature sintering stage is performed, in which the temperature is raised from 900° C. to 1300° C. at a heating rate of 8° C. per minute and maintained for 3 to 4 hours, so that the nano copper particles form a continuous heat conduction network in the alumina powder through liquid phase diffusion; S144. During the high-temperature sintering stage, a nitrogen protective atmosphere is maintained in the high-temperature sintering furnace to prevent oxidation of the nano-copper particles, and the polymethacrylate is volatilized at high temperature, so that the powder blank forms a uniformly distributed microporous structure; S145. After the high temperature sintering stage is completed, a slow cooling stage is performed, in which the temperature is slowly lowered to room temperature at a cooling rate of 5° C. per minute.

6. The method for preparing a multi-layer composite circuit board according to claim 1, characterized in that: Before S200, an insulating material is mixed with an electrical insulating filler to obtain an insulating coating material, and the insulating coating material is coated on the surfaces of a plurality of thermally conductive microporous ceramic materials. S200 specifically includes: S210, stacking a plurality of thermally conductive microporous ceramic materials and placing them into a vacuum hot press, and hot pressing the stacked plurality of thermally conductive microporous ceramic materials into a composite substrate by the vacuum hot press; S220, drilling holes on the composite substrate by using a laser drilling device to form thermal via holes penetrating the composite substrate, and performing ultrasonic cleaning on the composite substrate with the thermal via holes to remove debris and impurities generated during the drilling process; S230, after the composite substrate with the thermal via hole is cleaned, metallizing the inner wall of the thermal via hole to uniformly form a copper film with thermal conductivity and electrical connection performance on the inner wall of the thermal via hole; S240, after a copper film is formed on the inner wall of the thermal via hole, the composite substrate is placed in a high-temperature annealing furnace and annealed at 300° C. to 500° C. for 1 hour. During the annealing process, the copper film on the inner wall of the thermal via hole is combined with the continuous heat conduction network formed by the nano copper particles in the composite substrate to form a continuous heat conduction path.

7. The method for preparing a multi-layer composite circuit board according to claim 6, characterized in that: The S230 specifically includes: S231, immersing the cleaned composite substrate in a chemical plating solution containing copper ions, and uniformly depositing a copper film having thermal conductivity and electrical connection properties on the inner wall of the thermal via hole; S232, electroplating the thermal via hole on which a layer of copper film is deposited, and the thickness of the copper film on the inner wall of the thermal via hole is further increased by electroplating.

8. The method for preparing a multi-layer composite circuit board according to claim 1, characterized in that: The S300 specifically includes: S310, mixing the polyurethane particles and the carbon fiber filler according to a mass ratio to obtain a composite material for preparing a microporous layer; S320, placing the composite material for preparing the microporous layer in a mold for pre-pressing to obtain the microporous layer; S330, placing the microporous layer between adjacent layers of the composite substrate, bonding the microporous layer to the adjacent composite substrate by coating the surface of the microporous layer with silicone-based adhesive, and then performing vacuum hot pressing to form a multi-layer structure, performing corrosion-resistant coating on the surface of the multi-layer structure, and obtaining a multi-layer composite circuit board substrate.

9. A multi-layer composite circuit board, characterized in that: The multilayer composite circuit board is prepared by the method for preparing the multilayer composite circuit board according to claims 1-8, wherein the multilayer composite circuit board comprises: Thermally conductive microporous ceramic material, made by hot pressing a mixture of alumina powder and nano copper particles, used for lamination and vacuum hot pressing to form a composite substrate; A continuous heat-conducting network and microporous structure are formed in the thermally conductive microporous ceramic material to provide a heat conduction path and absorb external mechanical shock; Thermal vias are provided on the surface of the composite substrate and are connected to the continuous thermal conductive network to form a continuous thermal conductive path to improve thermal conductivity and electrical connection performance; The microporous layer is disposed between the composite substrates to optimize shock absorption performance and thermal stability.

Citation Information

Patent Citations

  • Low temperature sintered Ni metal fiber composite ceramic substrate

    CN103332942A

  • Method for high-precision alignment stacking of multilayer heterogeneous cooked ceramic substrates

    CN112074106A

  • High-frequency microwave printed circuit board with high heat dissipation performance and preparation method thereof

    CN118973157A

  • Process for the production of composite ceramic printed wiring board

    US20020040522A1

Cited By

  • Press-fit preparation method of high-thermal-conductivity circuit board and high-thermal-conductivity circuit board

    CN120018396A

  • A method for preparing a high thermal conductivity circuit board by pressing and a high thermal conductivity circuit board

    CN120018396B